Salivary Cortisol and Cold Pain Sensitivity in Female Twins. Issue 2 (17th August 2013) - Godfrey, Kathryn M.; Strachan, Eric; Dansie, Elizabeth; Crofford, Leslie J.; Buchwald, Dedra; Goldberg, Jack; Poeschla, Brian; Succop, Annemarie; Noonan, Carolyn; Afari, Niloofar
Abstract: Background: There is a dearth of knowledge about the link between cortisol and pain sensitivity. Purpose: We examined the association of salivary cortisol with indices of cold pain sensitivity in 198 female twins and explored the role of familial confounding. Methods: Three-day saliva samples were collected for cortisol levels and a cold pressor test was used to collect pain ratings and time to threshold and tolerance. Linear regression modeling with generalized estimating equations examined the overall and within-pair associations. Results: Lower diurnal variation of cortisol was associated with higher pain ratings at threshold ( p = 0.02) and tolerance ( p < 0.01). The relationship of diurnal variation with pain ratings at threshold and tolerance was minimally influenced by familial factors (i.e., genetics and common environment). Conclusions: Understanding the genetic and non-genetic mechanisms underlying the link between HPA axis dysregulation and pain sensitivity may help to prevent chronic pain development and maintenance.